The Role of Information Technology in Explaining the Impact of Artificial Intelligence on Enhancing the User Experience of Generation Z Social Media Users in Semarang City - Danna Wahyuni; Hendar Hendar (Green Publisher Indonesia, 2025)
This study aims to explain the role of information technology in mediating the impact of artificial intelligence on enhancing user experience among Generation Z social media users in Semarang City. The research employs a quantitative approach with an explanatory research method, involving 200 respondents from Generation Z who are active users of the Shopee e-commerce platform. Data were collected through online questionnaires and analyzed using the Partial Least Squares (PLS 4.0) method. The results of the study show that artificial intelligence has a positive and significant effect on user experience in social media. Artificial intelligence has a positive and significant effect on augmented reality. Artificial intelligence has a positive and significant effect on virtual influencers. Artificial intelligence has a positive and significant effect on chatbots. Augmented reality has a positive and significant effect on user experience in social media. Virtual influencers have a positive and significant effect on user experience in social media. Chatbots have a positive and significant effect on user experience in social media.